1985
DOI: 10.1200/jco.1985.3.8.1142
|View full text |Cite
|
Sign up to set email alerts
|

Selection bias in clinical trials.

Abstract: Of 90 patients with intermediate or high-grade sarcoma eligible for a randomized trial of adjuvant doxorubicin (Adriamycin, Adria Laboratories, Columbus, Ohio), 48 were not entered: 24 (27%) by physician's choice and 24 refused randomization. Sixty-five percent of lower stage patients were randomized compared with 37% of those with higher stage (P = .02). Patients with extremity lesions were more frequently offered participation in the study (P = .07). Patients with lower stage lesions accepted randomization m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
68
1
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(73 citation statements)
references
References 13 publications
2
68
1
2
Order By: Relevance
“…However, for most trials, no records concerning non-included eligible and ineligible patients are kept (3), and assessments of the generalizability of trial results are thus not possible or at least limited. Better survival for trial patients as compared to eligible non-participants has, however, been demonstrated in a nephroblastoma trial (12), a sarcoma trial (1), and a pooled analysis of several non-small cell lung cancer trials (11). These observations are supported by our analysis.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…However, for most trials, no records concerning non-included eligible and ineligible patients are kept (3), and assessments of the generalizability of trial results are thus not possible or at least limited. Better survival for trial patients as compared to eligible non-participants has, however, been demonstrated in a nephroblastoma trial (12), a sarcoma trial (1), and a pooled analysis of several non-small cell lung cancer trials (11). These observations are supported by our analysis.…”
Section: Discussionsupporting
confidence: 80%
“…The pretreatment characteristics of randomized and excluded patients may differ substantially with respect to clinical variables that potentially affect outcome (29). Patients who are willing to be entered into clinical trials differ from those who refuse randomization (1,5,6,30), as con rmed by our study. However, for most trials, no records concerning non-included eligible and ineligible patients are kept (3), and assessments of the generalizability of trial results are thus not possible or at least limited.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations